HUBUNGAN PENGETAHUAN DAN SIKAP KELUARGA TERHADAP PENCEGAHAN DYSPEPSIA DI DESA MATITI I KECAMATAN DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN TAHUN 2024 - Simamora, Rouli DF; Tambunan, Glorya; Br.Lumban Tobing, Tiara Pebrina; Banjarnahor, Jefri (Sekolaah Tinggi Ilmu Kesehatan (STIKes) Kesehatan Baru Doloksanggul, 2024)
Background: Dyspepsia is one of the factors that is a health problem in the community. This is a health problem that becomes an emergency unit channel on physical examination found a feeling of tenderness in the epigastric area leading to a diagnosis of gastritis. Purpose: The purpose of this study was to determine the Relationship between Knowledge and Community Attitudes Towards Dyspepsia Prevention. This type of research is quantitative research with an ascendental sampling design looking at the relationship between independent variables (knowledge, attitudes) with dependent variables (dyspepsia prevention) and then analyzing the data using a frequency distribution table, namely measurements at the same time to determine